2020
DOI: 10.1186/s40560-020-00478-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal cardiopulmonary resuscitation without target temperature management for out-of-hospital cardiac arrest patients prolongs the therapeutic time window: a retrospective analysis of a nationwide multicentre observational study in Japan

Abstract: Background: Extracorporeal cardiopulmonary resuscitation (ECPR) with extracorporeal membrane oxygenation (ECMO) is a promising therapy for out-of-hospital cardiac arrest (OHCA) compared with conventional cardiopulmonary resuscitation (CCPR). The no and low-flow time (NLT), the interval from collapse to reperfusion to starting ECMO or to the return of spontaneous circulation (ROSC) in CCPR, is associated with the neurological outcome of OHCA. Because the effects of target temperature management (TTM) on the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In terms of primary outcome, good neurologic outcome at hospital discharge was reported in 2 studies [ 19 , 23 ], while 5 studies reported it at 1 month [ 20 , 22 , 25 , 28 , 30 ], 3 studies at 3 months [ 26 , 28 , 30 ], and 2 studies at 6 months [ 20 , 27 ]; 2 studies reported survival to discharge as their primary outcome [ 7 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of primary outcome, good neurologic outcome at hospital discharge was reported in 2 studies [ 19 , 23 ], while 5 studies reported it at 1 month [ 20 , 22 , 25 , 28 , 30 ], 3 studies at 3 months [ 26 , 28 , 30 ], and 2 studies at 6 months [ 20 , 27 ]; 2 studies reported survival to discharge as their primary outcome [ 7 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis included six registry-based studies—four based in Japan, one in Paris, France, and one in Seoul, South Korea [ 20 , 21 , 23 , 25 , 27 , 30 ]. No additional studies from Paris or France were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations